2014
DOI: 10.1371/journal.pone.0105814
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Constitutive Neutrophil Apoptosis Due to House Dust Mite Allergen in Normal and Allergic Rhinitis Subjects

Abstract: House dust mite (HDM) is a primary allergen in allergic rhinitis (AR) and asthma. Neutrophil apoptosis is associated with allergic diseases and innate immunity to infection. The present study examined how HDM affects constitutive neutrophil apoptosis in normal and AR subjects. Total IgE increased in AR subjects when compared to normal subjects, and patients with AR were HDM-specific IgE positive (+), which is specific IgE to Dermatophagoides pteronissinus and Dermatophagoides farinae. In normal and AR subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
3
24
0
1
Order By: Relevance
“…A peak in the number of neutrophils was found during the period of maximal HDM-allergic inflammation 14. It is reported that Der p has anti-apoptotic effects on neutrophils through the toll-like receptor 4 (TLR4)/protein kinase C (PKC)δ/extracellular signal-regulated kinase (ERK)/nuclear factor-kappa B (NF-κB) pathway, which may prolong the survival time of local neutrophils 17. In addition, interleukin (IL)-17 is increased in AR patients, which could recruit a large number of neutrophils 18.…”
Section: Discussionmentioning
confidence: 99%
“…A peak in the number of neutrophils was found during the period of maximal HDM-allergic inflammation 14. It is reported that Der p has anti-apoptotic effects on neutrophils through the toll-like receptor 4 (TLR4)/protein kinase C (PKC)δ/extracellular signal-regulated kinase (ERK)/nuclear factor-kappa B (NF-κB) pathway, which may prolong the survival time of local neutrophils 17. In addition, interleukin (IL)-17 is increased in AR patients, which could recruit a large number of neutrophils 18.…”
Section: Discussionmentioning
confidence: 99%
“…Der p 2 is an essential allergen, which binds to serum IgE of allergy patients. We previously demonstrated that allergic disease is associated with regulation of neutrophil apoptosis and HDM, and that HDM inhibits the spontaneous apoptosis of neutrophils by cytokine secretion of lymphocytes via PAR2 [16,17]. In this study, we examined that Der p 2 regulates neutrophil apoptosis by inducing cytokine production in lymphocytes.…”
Section: Discussionmentioning
confidence: 96%
“…The antiapop totic signal due to DP is associated with activation of TLR4, PI3K, Akt, ERK, and NF-κB (Figure 4). The HDM mediated antiapoptotic effect through TLR4 in neutrophil apoptosis and PI3K, ERK, and NF-κB is as sociated with eosinophil apoptosis 18,26 . DP also medi ates the antiapoptotic signal by inhibiting the cleavage of procaspase 3 and procaspase 9 ( Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…Production of HDM IgE after exposure to HDM is consistently related to asthma development and exacerbation, and therefore used in the diagnosis, treatment and management of asthma 4,16,17 . We recently identified an antiapoptotic effect of DP on neutrophil apoptosis in allergic diseases 18 . Based on these findings, we investigated whether HDM is involved in pathoge nesis and exacerbation of asthma by inhibiting eosino phil apoptosis.…”
Section: Discussionmentioning
confidence: 99%